ANALISIS PENERAPAN PSAK 109 PADA LEMBAGA AMIL ZAKAT (Studi Kasus Pada LAZIS Sabilillah Kota Malang) - Eko Saputro; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to analyze the suitability of the concept ofrecognition, measurement, presentation and disclosure of zakat managementinstitutions. The object and location of this study were LAZIS Sabilillah Malang.Recognition is the recording of a number of rupiah into the accounting system sothat the amount will affect a post and is reflected in the financial statements.Measurement is the determination of the amount of rupiah that must be attachedto an object involved in a financial transaction. The presentation is set about waysto report elements or posts in a set of financial statements so that the elements orposts are informative enough. Whereas Disclosures relate to how to discloseexplanations of informative matters that are considered important and useful forusers other than what can be stated through the main financial statements. Thistype of research includes case study research using analytical descriptivemethods. The object and location of this study were LAZIS Sabilillah Malang. Inthis study data collection techniques using literature study, interviews anddocumentation. The analysis technique used in the study is by using descriptiveanalytical methods. The results of this study show that the recognition andmeasurement of zakat, charity infaq LAZIS Sabilillah Malang has not been fully inaccordance with the concept of recognition and measurement in PSAK 109, thepresentation concept of LAZIS Sabilillah Malang is in accordance with theconcept of presentation in PSAK 109, and the concept of LAZIS Sabilillah Malangdisclosure is not in accordance with the concept of disclosure in PSAK 109.Keywords: Recognition, measurement, presentation and disclosure